The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijerph17186886
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Patient-Centred Medical Home-Based Models of Care versus Standard Primary Care in Chronic Disease Management: A Systematic Review and Meta-Analysis of Randomised and Non-Randomised Controlled Trials

Abstract: Patient-centred care by a coordinated primary care team may be more effective than standard care in chronic disease management. We synthesised evidence to determine whether patient-centred medical home (PCMH)-based care models are more effective than standard general practitioner (GP) care in improving biomedical, hospital, and economic outcomes. MEDLINE, CINAHL, Embase, Cochrane Library, and Scopus were searched to identify randomised (RCTs) and non-randomised controlled trials that evaluated two or more prin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 118 publications
(263 reference statements)
1
50
0
Order By: Relevance
“…Wagner et al also emphasized the importance of tailored care planning to support survivors' self-management and help them and their supportive others cope with chronic illness ( 56 ). Tailored care planning can further enhance health-related quality of life, reduce depression and reduce healthcare costs related to visits to emergency departments ( 57 , 58 ). It has also been suggested that compared to usual care individualized care plans can lower distress scores and improve the mental domain of QoL among HSCT-survivors 1–5 years post-transplant ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wagner et al also emphasized the importance of tailored care planning to support survivors' self-management and help them and their supportive others cope with chronic illness ( 56 ). Tailored care planning can further enhance health-related quality of life, reduce depression and reduce healthcare costs related to visits to emergency departments ( 57 , 58 ). It has also been suggested that compared to usual care individualized care plans can lower distress scores and improve the mental domain of QoL among HSCT-survivors 1–5 years post-transplant ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis concluded that person-centered care is more effective than standard healthcare for people diagnosed with depression, improving depressive symptoms and increasing the likelihood of remission [15]. In addition, he concluded that this type of care improves health-related quality of life and self-management results and decreases hospital admissions [15].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis concluded that person-centered care is more effective than standard healthcare for people diagnosed with depression, improving depressive symptoms and increasing the likelihood of remission [15]. In addition, he concluded that this type of care improves health-related quality of life and self-management results and decreases hospital admissions [15]. A study on late-life depression highlighted, as priority areas of research to improve health services for this clinical condition, the focus on the individual needs of the person, through patient-centered care [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is based on key attributes such as access to a primary care physician, patient-centeredness, comprehensive and coordinated care, accessible services, and a commitment to quality and safety [1]. PCMH is associated with not just positive health outcomes at the primary care level but also reduced healthcare utilization at the tertiary level [2,3]. Therefore, in 2011 Singapore's Ministry of Health (MOH) introduced the Family Medicine Clinic (FMC) as its localized version of PCMH to enhance chronic disease management in the primary care level [4].…”
Section: Introductionmentioning
confidence: 99%